Joking Asides : The Theory, Analysis, and Aesthetics of Humor - Oring, Elliott, 1945- (Book collections on Project MUSE., 2016)
"Oring analyzes key contemporary approaches to the study of humor and addresses controversial topics with new empirical data and insight. He tests appropriate incongruity against other major positions in the field, including Semantic Script Theory, the General Theory of Verbal Humor, Conceptual Integration Theory, and Benign Violation Theory"--Provided by publisher